Meminimalisasi Frekuensi Downtime pada Mesin Ayakan Pellet 7 di PT Charoen Pokphand Indonesia Feedmill Balaraja - Ivan Yosia Raharjo; I Nyoman Sutapa (Jurnal Titra, 2018)
PT. Charoen Pokphand Indonesia Feedmill is one of the largest animal feed companies in Indonesia. One of the obstacles experienced by PT. Charoen Pokphand Indonesia Feedmill Balaraja is the downtime due to the replacement of the (sifter change) sieve fabric that is on the pellet machine 7. The frequency of downtime caused by the replacement (sifter change) of this sieve cloth occurs 2-3 times in 1 month. The method used to solve and analyze downtime problems is to use DMAIC with the five why's Analyze tool. There are several factors that cause downtime because the fabric is not strong vibration sieve, the fabric is too tight, and blacu material is not durable. Proposed improvements made is to install verloop and change the installation method of the sieve fabric. The result of the improvement is reduced the frequency of downtime to 2 times in 2 months and reduce waste cost. The Results of the implementation will be compared in the last 2 months, February and March 2018, company achieve cost savings Rp. 194.645.793,00 in terms of pellet, while in terms of packging Rp. 193.208.052,00. Another Sugesstion is to control the sieve fabric by the checklist.